1999
DOI: 10.1099/0022-1317-80-1-169
|View full text |Cite
|
Sign up to set email alerts
|

A divergent genotype of hepatitis E virus in Chinese patients with acute hepatitis.

Abstract: Recent studies have reported and provided nucleotide sequence data from divergent isolates of hepatitis E virus (HEV), including isolates from North America and Africa. Sera were investigated from 29 Chinese patients with a diagnosis of acute hepatitis and who were negative for hepatitis viruses A-E by serology (HEV was excluded by testing for IgG antibody only). To determine whether some patients were infected with HEV but had yet to seroconvert to antibody positivity, RT-PCR was carried out with primers desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
186
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(193 citation statements)
references
References 23 publications
5
186
0
2
Order By: Relevance
“…HEVs can be classified into 4 genotypes based on the phylogenetic analysis of the viral genomes. The Burmese, Mexican, American, and Chinese HEV strains are the prototype of genotypes 1, 2, 3, and 4, respectively [6,18,19,23]. Genotype 1 HEV was isolated from several countries in Asia and Africa, genotype 2 was from Mexico, Nigeria, and Chad, genotype 3 was from a lot of countries in America, Asia, Europe, and Oceania, and genotype 4 was exclusively from Asian countries [10].…”
mentioning
confidence: 99%
“…HEVs can be classified into 4 genotypes based on the phylogenetic analysis of the viral genomes. The Burmese, Mexican, American, and Chinese HEV strains are the prototype of genotypes 1, 2, 3, and 4, respectively [6,18,19,23]. Genotype 1 HEV was isolated from several countries in Asia and Africa, genotype 2 was from Mexico, Nigeria, and Chad, genotype 3 was from a lot of countries in America, Asia, Europe, and Oceania, and genotype 4 was exclusively from Asian countries [10].…”
mentioning
confidence: 99%
“…As for other possibilities, the involvement of a third, previously unrecognized, enterically transmitted hepatitis agent, whose existence was suggested by Arankalle et al (1994), and non-viral agents such as Gram-negative bacilli that are known to cause hepatitis (El-Newihi et al, 1996), need to be taken into consideration in some patients with acute hepatitis of unknown aetiology, since the clinical picture, age distribution and seasonal distribution of patients with non-A to E hepatitis in Nepal were similar to those of patients with hepatitis E (data not shown Gouvea et al (1997Gouvea et al ( , 1998 and Shrestha et al (2003), but HEV 1c had not been identified in Nepal. To date, HEV 1c has been isolated in India and mainland China (Wang et al, 1999), suggesting that the 1c strain(s) was imported from India or China to Nepal in 1997 or before, but was taken over by the co-circulating 1a strains in 1999. As HEV 1a strains were isolated from patients in all four years studied, comparative sequence analysis was restricted to HEV 1a isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The observed changing prevalence of the five 1a clusters according to the year of disease onset suggests that the genetic variability of HEV in a community is due to continuously occurring genetic changes and that takeover of existing strain(s) possibly occurs by the selected variant having an advantage in transmission in the community or variant(s) that was imported from other communities. An alternative hypothesis for the variability observed in field isolates is ongoing evolution in alternative host species, since increasing evidence has indicated that hepatitis E is a zoonosis (Harrison, 1999;Erker et al, 1999;Meng, 2000;Meng et al, 1997Meng et al, , 1998Halbur et al, 2001;Okamoto et al, 2001;Smith, 2001;Takahashi et al, 2003;Tei et al, 2003), whether or not hepatitis E is common in the resident human population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is interesting that diverse HEV isolates belonging to genotypes 1 and 4 co-exist in China. HEV isolates from epidemic areas initially identified in China were classified into genotype 1 (21), whereas recently identified HEV isolates from sporadic cases were assigned to genotype 4 (22,23).…”
Section: Introductionmentioning
confidence: 99%